CHA2DS2-VASc score predicts the slow flow/no-reflow phenomenon in ST-segment elevation myocardial infarction patients with multivessel disease undergoing primary percutaneous coronary intervention. Issue 21 (28th May 2021) - Huang, Xin; Zheng, Wen; Zhao, Xue Dong; Nie, Shao Ping
Abstract : Abstract: ST-segment elevation myocardial infarction (STEMI) patients with multivessel disease (MVD) have a higher incidence of slow-flow/no-reflow (SF-NR) phenomenon during primary percutaneous coronary intervention (PPCI) than those with single vessel disease. Currently, no effective tools exist to predict the risk of SF-NR in this population. The present study aimed to evaluate whether CHA2 DS2 -VASc score can be used as a simple tool to predict this risk. This study consecutively included STEMI patients hospitalized in Beijing Anzhen Hospital from January 2005 to January 2015. Among these patients, 1032 patients with MVD were finally enrolled. Patients were divided into SF-NR (+) group and SF-NR (–) group according to whether SF-NR occurred during PPCI. SF-NR was defined as the thrombolysis in myocardial infarction (TIMI) grade ⩽2. There were 134 patients (13%) in the SF-NR (+) group. Compared with the SF-NR (–) group, patients in the SF-NR (+) group are elder, with lower left ventricular ejection fraction and higher CHA2 DS2 -VASc score. Multiple logistic regression analysis indicated that CHA2 DS2 -VASc score ≥3 (odds ratio [OR], 2.148; 95% confidence interval [CI], 1.389–3.320; P = .001), current smoking (OR, 1.814; 95% CI, 1.19–2.764; P = .006), atrial fibrillation (OR, 2.892; 95% CI, 1.138–7.350; P = .03), complete revascularization (OR, 2.307; 95% CI, 1.202–4.429; P = .01), and total length of stents ≥40 mm (OR, 1.482; 95% CI, 1.011–2.172; P = .04) were independent risk factors of SF-NR. The incidence of SF-NR in patients with CHA2 DS2 -VASc score ≥3 was 1.7 times higher than that in patients with CHA2 DS2 -VASc score <3. Additionally, patients with CHA2 DS2 -VASc score ≥3 plus ≥2 risk factors have 3 times higher incidence of SF-NR than those with CHA2 DS2 -VASc score ≥3 plus 0 to 1 risk factor. CHA2 DS2 -VASc score ≥3 can be used as a simple and sensitive indicator to predict SF-NR phenomenon and guide the PPCI strategy in STEMI patients with MVD.